MPDZ promotes DLL4-induced Notch signaling during angiogenesis - Tetzlaff, Fabian; Fischer, Andreas (eLife, 2018)
Angiogenesis is coordinated by VEGF and Notch signaling. DLL4-induced Notch signaling inhibits tip cell formation and vessel branching. To ensure proper Notch signaling, receptors and ligands are clustered at adherens junctions. However, little is known about factors that control Notch activity by influencing the cellular localization of Notch ligands. Here, we show that the multiple PDZ domain protein (MPDZ) enhances Notch signaling activity. MPDZ physically interacts with the intracellular carboxyterminus of DLL1 and DLL4 and enables their interaction with the adherens junction protein Nectin-2. Inactivation of the MPDZ gene leads to impaired Notch signaling activity and increased blood vessel sprouting in cellular models and the embryonic mouse hindbrain. Tumor angiogenesis was enhanced upon endothelial-specific inactivation of MPDZ leading to an excessively branched and poorly functional vessel network resulting in tumor hypoxia. As such, we identified MPDZ as a novel modulator of Notch signaling by controlling ligand recruitment to adherens junctions.